Probing of Reorganization Dynamics within the Different Phases of Themotropic Liquid Crystals. Issue 5 (6th February 2018) - Panda, Manas Ranjan; Koley, Somnath; Mishra, Krishna; Ghosh, Subhadip
Abstract: Solvent properties of two liquid crystalline solvents (LCs), 4‐n‐pentyl‐4 / ‐cyanobiphenyl (5CB) and 4‐n‐octyl‐4 / ‐cyanobiphenyl (8CB) are studied by exploiting their intrinsic fluorescence. Solvation dynamics of LCs in crystalline, liquid crystalline and liquid phases are observed by utilizing the dynamic Stokes shift in the time resolved emission spectrum (TRES) of an excited dye molecule coumarin 153 (C153) immersed within the LCs. With increasing temperature, transitions occur from crystalline to smectic/nematic and finally to liquid phase for these thermotropic LCs. At high temperature, liquid crystalline phases with substantial orientational orders are transformed to isotopic liquid phases. In this phase, peak positions of intrinsically fluorescent LCs are shifted towards the higher energy side with lowering its fluorescence quantum yields (φf ) as compared to the emission peak positions and quantum yields of LCs in other anisotropic phases. Solvation dynamics study shows that the average solvation time of C153, immersed within the liquid phases of LCs, is about an order of magnitude faster as compared to that within a crystalline phase of the same substrate (5CB or 8CB). This observation is substantiating the fact that even within a complete crystalline phase a fluid like motion of the LC solvent molecules still exists. Average solvation time of C153 follows a descending order when we move from a complete crystalline phase to liquid crystalline phase to complete liquid phase. Abstract : The reorganization dynamics of liquid crystal molecules around the excited state dipole of a probe behaves in a very different way in nematic phase than the isotropic phase. Reorganization time scales of liquid crystal molecules are largely controlled by the phase behaviors.